Journal of Human Sport and Exercise - 2019 - Spring Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc4.46
|View full text |Cite
|
Sign up to set email alerts
|

Development of motor skills applied to basketball in the developmental age

Abstract: Usually, the training planning large amounts of technical skills and tactical work are planned, neglecting the part of athletic physical training, while it is necessary to combine the athletic phase with the technical one according to principle of the complexity of the sports performance that integrates the quantitative part with to the qualitative one. The study aims to show whether specific workouts aimed at developing and consolidating the basic motor patterns then lead to an improvement in performance in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Findings reveal that both groups have significant differences in their shooting accuracy, with the posttest result showing significantly higher shooting accuracy than the pretest result. (Montella et al, 2019). This emphasizes that good shooting improvement interventions like form shooting, shooting with a partner, and shooting off dribble improve the mechanics and coordination of the shooting action.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings reveal that both groups have significant differences in their shooting accuracy, with the posttest result showing significantly higher shooting accuracy than the pretest result. (Montella et al, 2019). This emphasizes that good shooting improvement interventions like form shooting, shooting with a partner, and shooting off dribble improve the mechanics and coordination of the shooting action.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Stability exercise is the ability to stand or move while staying in control of the body position and keeping balance. The Principle of Motor Learning by (Montella et al, 2019) states that corrective exercises might make people more accurate with shooting skills as they break down complicated actions into smaller, easier-to-control parts that can be practiced repeatedly.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…To our knowledge, only a few studies have aimed to determine the relationship between the functional classification level and sport-specific skill tests. Previous research has shown that trunk impairment impacted wheelchair propulsion, especially in acceleration from a standstill (Montella et al, 2019;Tafuri et al, 2017). Similar to our study, De Groot et al (2012) did not find any differences between the players of a low (<4) and high (>4) IWBF classification level in short-term performance field-based tests.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of adequate equipment is essential even if in Italian public elementary schools, it is often lacking especially with regard to small tools and carpets. The availability of suitable and preparatory environments and equipment can only facilitate the learning of skills (Montella, Ceciliani, Morsanuto, Federici, & Altavilla, 2019). In addition to the traditional gym equipment that is usually divided into large tools (wall bars; Swedish framework: climb stage, vertical stairs, horizontal ladder, boards and balance beam, pony, small and large mattresses) and small tools (filled balls or «medicine balls», light balls, tennis balls, ropes, logs; reek and boards; hoops: clubs) each teacher can add any other unconventional tool.…”
Section: The Value Of Indoor Space In Motor Learningmentioning
confidence: 99%